Multi-objective Optimization Configuration of Capacitor Blocking Devices based on Field-Circuit Coupled Model and Improved Differential Evolution Algorithm. Issue 4 (May 2019) - Zeng, Wenhui; Ren, Hao; Tang, Yang; Ni, Jiang; Chen, Xin
Abstract: The dc current of grounding pole will invade the transformer windings nearby when the HVDC system is in ground return operation, which will cause DC bias and affect the safety and stability of the system. It is an effective method to restrain dc current in transformer to install capacitor blocking devices at transformer neutral wire, but it is shown that this may increase the bias current of nearby transformers. For this reason, the installation of blocking device in a certain area can be considered as an optimization problem. An improved differential evolution algorithm is proposed to optimize the multi-objective configuration of capacitor blocking devices to suppress DC bias globally. The field-circuit coupled model is established to solve the potential. The objective function is to minimize the number of installations of the devices and the absolute sum of the total DC current of the transformer in the region, and the constraint is all DC current at the neutral point of each transformer is under the limit, then the optimal configuration model is established. Finally, the chaos mapping theory, adaptive parameters and elitism preservation strategy are introduced into the difference evolution algorithm to solve the model and obtain the optimal allocation scheme.